A Lifestyle-Based Perspective on the Mobility Choices and Preferences of Urban Travelers - Maria Chatziathanasiou; George Botzoris; Maria Morfoulaki; Kornilia-Maria Kotoula (Applied Sciences)
This study investigates how lifestyle factors influence mobility choices within the metropolitan area of Thessaloniki, which is the second largest city in Greece. The primary objective is to understand the interplay between lifestyle attitudes and preferences for sustainable mobility options. This research utilizes data from a comprehensive survey conducted among Thessaloniki’s inhabitants, identifying four distinct attitudinal clusters shaped by lifestyle characteristics and general attitudes toward recycling, energy conservation, social distancing, and other factors. A two-step clustering approach combining hierarchical and k-means methods as well as Chi-square and Kruskal–Wallis tests were employed to investigate whether life attitudes are correlated with revealed and stated mode choices as well as beliefs, perceptions, and feelings related to the current and future public transport systems and micromobility options in the metropolitan area of Thessaloniki. The findings reveal significant variations in mobility choices across the identified lifestyle segments with environmentally conscious segments showing a higher propensity for sustainable modes of transport. Additionally, differences are observed in perceptions and intentions regarding micromobility and the future mass transit system within the region, suggesting that when introducing a new metro system that is expected to promote a shift toward public transport, segment-specific approaches are necessary for raising awareness and increasing trust to the new mode.